2013
DOI: 10.1111/mec.12230
|View full text |Cite
|
Sign up to set email alerts
|

The hindgut lumen prokaryotic microbiota of the termite Reticulitermes flavipes and its responses to dietary lignocellulose composition

Abstract: Reticulitermes flavipes (Isoptera: Rhinotermitidae) is a highly eusocial insect that thrives on recalcitrant lignocellulosic diets through nutritional symbioses with gut-dwelling prokaryotes and eukaryotes. In the R. flavipes hindgut, there are up to 12 eukaryotic protozoan symbionts; the number of prokaryotic symbionts has been estimated in the hundreds. Despite its biological relevance, this diverse community, to date, has been investigated only by culture- and cloning-dependent methods. Moreover, it is uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 93 publications
10
100
1
Order By: Relevance
“…Bacteroidetes were found in low concentrations (1 %) in R. lucifugus, in contrast to the abundance found in Reticulitermes santonensis (Feytaud) (Yang et al 2005) and R. flavipes (Boucias et al 2013). Members of the phylum Bacteroidetes have been reported to reside in the gut as ecto-or endosymbionts of flagellated protozoa (Noda et al 2005;Nakajima et al 2006), and cellularlevel symbioses between Bacteroidales and gut protists are as common as those between spirochetes and gut protists.…”
Section: Resultsmentioning
confidence: 69%
“…Bacteroidetes were found in low concentrations (1 %) in R. lucifugus, in contrast to the abundance found in Reticulitermes santonensis (Feytaud) (Yang et al 2005) and R. flavipes (Boucias et al 2013). Members of the phylum Bacteroidetes have been reported to reside in the gut as ecto-or endosymbionts of flagellated protozoa (Noda et al 2005;Nakajima et al 2006), and cellularlevel symbioses between Bacteroidales and gut protists are as common as those between spirochetes and gut protists.…”
Section: Resultsmentioning
confidence: 69%
“…Much evidence suggests that the bacterial diversity of the gut microbiota is essential for maintaining gut homeostasis (Boucias et al., 2013; Hu, Lukasik, Moreau, & Russell, 2014). In the gut of Reticulitermes flavipes termites, a diet of corn stover reduced the bacterial richness and diversity, compared with sorghum and two other woody diets (Huang et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly , the diet has significant effects on the gut microbiome of both lower and higher termites (Boucias et al., 2013; Huang, Bakker, Judd, Reardon, & Vivanco, 2013). For example, the gut bacterial community of the lower termite Reticulitermes flavipe can be differentiated on the basis of grassy and woody diets as well as among different grassy diets (Huang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that different dietary habits shape the structure of microbiota in the termite gut (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). Dietary manipulation induces measurable differences among gut bacterial communities, and the recalcitrance of plant substrates may be the major cause of this variation in the diversity and richness of gut bacterial communities (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). However, influences on the abundance and diversity of the intestinal microbial of termite fed with different substrates containing various lignin and cellulose or hemicellulose remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and complexity of the termite gut microbiota have been evaluated using molecular technology techniques based on 16S rRNA (Warnecke et al, 2007;Berlanga et al, 2011;Mathew et al, 2012). Recent studies have indicated that different dietary habits shape the structure of microbiota in the termite gut (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). Dietary manipulation induces measurable differences among gut bacterial communities, and the recalcitrance of plant substrates may be the major cause of this variation in the diversity and richness of gut bacterial communities (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013).…”
Section: Introductionmentioning
confidence: 99%